2014
DOI: 10.1177/0961203314559086
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the response to treatment in acute lupus hemophagocytic syndrome

Abstract: Low CRP and high hemoglobin can predict a positive response to corticosteroid monotherapy while high serum ferritin and low leukocyte count can predict a positive response to CsA in patients with ALHS and therefore, when corticosteroid monotherapy is not effective in such cases, CsA could be the first choice of an additional immunosuppressive agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…Haematological abnormalities, if relapsing or refractory to steroids, have been shown to respond well to CyA. This is the case of lupus-associated thrombocytopenia [93,94], haemolytic anaemia [95], aplastic anaemia [96], red cell aplasia [97][98][99] and haemophagocytic syndrome [100].…”
Section: Cyclosporine a In Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Haematological abnormalities, if relapsing or refractory to steroids, have been shown to respond well to CyA. This is the case of lupus-associated thrombocytopenia [93,94], haemolytic anaemia [95], aplastic anaemia [96], red cell aplasia [97][98][99] and haemophagocytic syndrome [100].…”
Section: Cyclosporine a In Systemic Lupus Erythematosusmentioning
confidence: 99%
“…However, we could not deny the possibility that the response of ALHS to first IVCY was delayed, second and third IVCY might have contributed to maintaining control of the patient's ALHS, while concomitant IVIG might have had synergistic effects on the activated macrophages. Indeed, our previous study revealed a significant and negative correlation between the serum ferritin and anti-dsDNA antibody levels among reviewed ALHS cases ( 12 ). Moreover, among 32 ALHS patients treated with CsA, the serum ferritin level was significantly higher and the leukocyte count was significantly lower in CsA responders than in non-responders ( 12 ).…”
Section: Discussionmentioning
confidence: 88%
“…HLH is a valid example of the plenty of still-open challenges we are facing in the field of autoimmune and autoinflammatory diseases. The Takahashi et al 10 study results allude to possible different sub-phenotypes of the same disease, which differently respond to a different therapeutic schedule. The identification of predictive markers for the treatment response and disease outcome helped in formulating this hypothesis, which still requires further confirmation.…”
mentioning
confidence: 99%
“…Similarly, between 2005 and 2013 Takahashi et al 10 reported seven patients diagnosed with ALHS, among whom five experienced ALHS as the first manifestation of SLE. Interestingly, cases with low anti-double-stranded DNA (anti-dsDNA) antibody titres tended to have more severe hyperferritinemia, and a negative and significant correlation between anti-dsDNA antibodies and levels of serum ferritin was finally found.…”
mentioning
confidence: 99%
See 1 more Smart Citation